Nrf2 Mediated Heme Oxygenase-1 Activation Contributes to Diabetic Wound Healing – an Overview - Ramachandran, Vadivelan; Mohanasundaram, Tharani; Tiwari, Ruchi; Tiwari, Gaurav; Vijayakumar, Putta; Bhongiri, Bhargav; Xavier, Rinu Mary (Drug Research, 2022)
Diabetic wound healing is a complicated procedure because hyperglycemia changes the various stages of wound healing. In type 2 diabetes mellitus (T2DM), oxidative stress is proven to be a critical factor in causing non-healing wounds and aggravating the inflammatory phase, resulting in the amputation of lower limbs in T2DM patients. This makes scientists figure out how to control oxidative stress and chronic inflammation at the molecular level. Nuclear factor erythroid 2- related factor 2 (Nrf2) releases antioxidant proteins to suppress reactive oxygen species (ROS) activation and inflammation. The current review discusses the role of Nrf2 in improving diabetic wound healing by reducing the production of ROS and thus reducing oxidative stress, as well as inhibiting nuclear factor kappa B (NF-kB) dissociation and nuclear translocation, which prevents the release of inflammatory mediators and increases antioxidant protein levels, thereby improving diabetic wound healing. As a result, the researcher will be able to find a more effective diabetic wound healing therapy.
Keywords: Nrf2; anti-oxidants; ROS; diabetic wound healing; anti-inflammatory; HO-1